KOMPETENSI PEDAGOGIK MAHASISWA TINGKAT AKHIR PROGRAM STUDI PENDIDIKAN TEKNIK MESIN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SARJANAWIYATA TAMANSISWA - Rabiman Rabiman; Slamet Priyanto (Jurnal Taman Vokasi, 2014)
Â  Â This study aimedÂ  to determine the level of the pedagogic competence of the final year students of Mechanical Engineering Education of Sarjanawiyata Tamansiswa University. This study is descriptive research. The study was conducted in Mechanical Engineering Education Sarjanawiyata Tamansiswa University in YogyakartaÂ  and The Vocational Educational School that became a partner in the implementation of the PPL II. The population were students of The Mechanical Engineering Education of Sarjanawiyata Tamansiswa University who were implemented the PPL II in odd semester academic year 2013/2014 as many as 92 people. Data collectedÂ  using the questionnaire method. As the data source is SMK students, students of Mechanical Engineering Education of Sarjanawiyata Tamansiswa University and teacher as PPL II tutor. Analysis using descriptive statistics. The results show that the pedagogic competence of the final year students of The Mechanical Engineering Education of Sarjanawiyata Tamansiswa University are; 1) according to the students of Mechanical Engineering Education of Sarjanawiyata Tamansiswa University is in â€œgoodâ€ category with an average value of 78%; 2) according to the students SMK is in â€œvery goodâ€ category with an average value ofÂ  82%; and 3) according to teacher as PPL II tutor is in â€œgoodâ€ categories with an average value of 77 %. This suggests that the provision granting pedagogical competence for the student of mechanical engineering UST Yogyakarta through Courses Education Group in general has been good and should continue to be improved in all aspects, so as to reach the level of competence in the very good category.